Effect of Force Molting on Blood Parameters of Broiler Breeder Hens - Khalid Hamid Hassan (Journal of Global Pharma Technology, 2018)
The study was conducted in the poultry house of animal production Department, College of Agriculture, University of Diyala, during the period 1st Oct. 2016 to 22 June 2017. The aim of the study was to determine the effect of force molting by fasting program of Ross 308 and Arbor Acres broiler breeder hens on blood parameters. The experiment consists of four groups (each group consist of 15 hens) namely Ross molting (Rm), Ross control (Rc), Arbor Acres molting (Am), and Arbor Acres control (Ac). The blood samples performed with three replications. The results were indicated that there is a significant higher heterophil cell count of Am compared with Rm, while there is higher Base cell and H/L of Am compared with other groups. Also, there is a significant superiority of Am and Rm in PCV and Hb values compared with other groups. There is a superiority of Ac and Rc in blood glucose, protein and globulin compared with other groups. There is a significant increase of WBC, Heterophil, Basophils, H/L, Hb in molting groups compared with control group, while there is a significant superiority of control groups compared with molting groups in glucose, albumin, cholesterol, GPT, GOT and uric acid. Keywords: Force molting, Arbor Acres, Ross 308, Blood parameters.